One public : New York's Public Theater in the era of Oskar Eustis - Landis, Kevin (Professor of Theatre) (Metheun Drama, 2022)
"While other books about the Public have focused on its founder, Joe Papp, One Public: New York's Public Theater in the Era of Oskar Eustis presents the broader institution and assesses how it has guided American theater making throughout the past 20 years. Framed by the tenure of its current Artistic Director, Oskar Eustis, the book tells Eustis' story, recorded over many interviews with practitioners and performers ranging from Diane Paulus, Tony Kushner and Lyn Nottage to Kevin Kline, Chelsea Clinton and Lin-Manuel Miranda. The Public Theater in New York recently passed two noteworthy milestones: the 60th anniversary of Shakespeare in the Park and the 50th anniversary of the Astor Place theatre premiere of Hair. By 2019, with the critical and financial success of Hamilton and Fun Home, the Public found itself at the center of American conversations about the way theater is nurtured and developed. With seven stages in New York City the Public Theater is synonymous with an array of theatrical work, and with the ravages of 2020, their original mission and mantra of theater by, for and about the people of New York, was challenged like never before in its history. Rather than a time-line history of the Public's output, this book is case-study driven, using interviews and authorial experience to illuminate the Public Theater and its cultural influence on the city of New York and the greater United States. Through expert commentary and analysis, combined with exclusive interview content, the book allows the reader to understand the challenges and contradictions of an institution at once creating commercial "uptown" theater, while espousing a mission of inclusivity and community-based development"--